TECHNIGUES USED FOR THE ACTIVATION OF COGNITIVE ACTIVITIES IN SENIOR PUPILS INVOLVED IN THE TEAM WORKING - Дорожко, Ірина; Малихіна, Олена; Туріщева, Людмила (New Collegium, 2020)
The team form of learning activities appeared as an alternative to the available traditional forms of teaching. Psychological and pedagogical research data show that team learning activities contribute to the activation and effectiveness of the teaching of schoolchildren, rearing humane interrelations between them, self-reliance, ability of pitching and espousing the standpoint of their own and also listening to the opinion of their comrades, rearing the dialoging culture, responsibility for the results of their work. Therefore, team learning activities is the form of learning organization for the small teams of students that are united by the common learning goal with the intermediate management of the teacher cooperating with them. Analyzing the available forms and methods of work used by the teachers in their activities we drew a conclusion on the insufficient amount of techniques that contribute to the activation of mental activities in pupils. For this purpose we developed “the labyrinth” that allows the team of students to pass through it. The “labyrinth” permits the solution of a number of problems with intricate moves and the students are supposed to manage the situation. “The labyrinth” developed by us consists of many problems that include in their turn the microproblems. The obtained results allowed us to define the following peculiarities of use of the “labyrinth” as a team working technique: Aspiration for the information exchange; Positive emotionality during the fulfillment of all the tasks; Mutual assistance during the discussion; Cooperation; some students felt the need for the explanation of the problem solution procedure to other students; Aspiration for the self-assertion.